Cesar Ita: capstone - Ita, Cesar, artist (Colorado State University. Libraries, 2017)
The artist's statement: My interest in drawing comes from the passion I have for representing the subtle yet distinct varieties of color and line through the use of varied media, especially colored pencil, acrylic, and ink on paper. Color and line are the two elements of art I excel in. I mostly draw non-representational subject matter with an emphasis in expressing geometric shapes. Architecture is a source of inspiration for me because I like structure. Another source of inspiration for me is the sublime. The sublime represented in my artwork is influenced by the Fibonacci number sequence as well as the phi ratio. Identity is another concept that I like to represent in my art through the rendition of abstract masks. Sacred geometry is another source of subject matter frequently spotted in my art. I like to experiment with patterns found in mathematical logarithms and play with quantities of a given element such as line. Chaos theory, metaphysics, spirituality, and psychedelics are heavy influences found in my art. I also like to experiment with the concepts of masculinity and femininity. A famous African American drag queen in a blonde wig once said, "Use every color in the crayon box." I will do just as this drag queen-RuPaul-said because life is not meant to be taken so seriously. And for that matter, art shouldn't be taken so seriously either. My ultimate goal as an artist, especially as an artist who draws, is to show the world that art can be anything you want it to be. Art has no rules. Art is the most freeing thing that anyone can take up. Long live art and long live the human condition of one who considers theirself an artist.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: drawing